Evaluation of Vegetation and Wildlife in Gunung Ambang Nature Reserve - Sudiyono, Sudiyono (Jurnal Wasian, 2014)
The objective of this research is to evaluate the ecosystem functions through vegetation and wildlife indicators.  Methods used are vegetation analysis and direct indirect method to count wildlife .  Results show that the dominant type of land coverage in Gunung Ambang Nature Reserve is open secondary forest, where shrubs, rattan, and epiphytes dominated.  This might lead to vulnerability of the site toward disturbance.  Furthermore, it was indicated that this area still contains local wildlife species such as Babyrousa babyrussa celebensis.  Eventhough land degradation has become a significant issue, the status of Gunung Ambang as nature reserve has limited restoration attempts both vegetatively and mechanically.